The Kondo effect of an adatom in graphene and its scanning tunneling spectroscopy - Lin Li; Yang-Yang Ni; Yin Zhong; Tie-Feng Fang; Hong-Gang Luo (New Journal of Physics, 2013)
We study the Kondo effect of a single magnetic adatom on the surface of graphene. The unique linear dispersion relation near the Dirac points in graphene makes it easier for the magnetic atom to form a local magnetic moment, which simply means that the Kondo resonance can be observed in a wider parameter region than in the metallic host. Our study indicates that the Kondo resonance, whenever the chemical potential is tuned away from the Dirac points, can indeed occur ranging from the Kondo regime, to the mixed valence, even to the empty orbital regime defined in the conventional metal host. While the Kondo resonance appears as a sharp peak in the Kondo regime, it has a peak-dip structure and/or an anti-resonance in the mixed valence and empty orbital regimes, which result from the Fano resonance due to the significant background due to dramatic broadening of the impurity level in graphene. We also study the scanning tunneling microscopy (STM) spectra of the adatom and they show obvious particle–hole asymmetry when the chemical potential is tuned by the gate voltages applied to the graphene. Finally, we explore the influence of the direct tunneling channel between the STM tip and the graphene on the Kondo resonance and find that the lineshape of the Kondo resonance is unaffected, which can be attributed to an unusually large asymmetry factor in graphene. Our study indicates that graphene is an ideal platform to systematically study Kondo physics and these results are useful to further stimulate relevant experimental studies on the system.